Hubungan Self Efficacy Terhadap Minat Berwirausaha Mahasiswa Program Studi Sarjana Terapan Kebidanan Kediri Poltekkes Kemenkes Malang - Shintya Okta Rihandhini; Dwi Estuning Rahayu; Susanti Pratamaningtyas; Ira Titisari (Lembaga Pengembangan Kinerja Dosen, 2025)
The high number of midwife graduates each year has led to an increase in unemployment in Indonesia, making it necessary to find ways to overcome this high unemployment rate. High unemployment will become a problem in itself in economic terms, leading to poverty and other social problems. Therefore, alternatives are needed to create businesses that will open up job opportunities for oneself and others through entrepreneurship. One such alternative is to become an entrepreneur by fostering an interest in entrepreneurship. Students' interest in entrepreneurship can be influenced by self-efficacy. To start and run a business, one needs the confidence that they will succeed. Self-efficacy can influence interest in entrepreneurship. The purpose of this study was to determine the relationship of self-efficacy with student entrepreneurial interest. This research is a cross-sectional approach, with a population of 90 people, then obtained a sample of 73 people using a proportionate stratified random sampling technique. The population of this study were students of the 2020 and 2021 Applied Bachelor's Degree Program of Midwifery in Kediri. Data obtained from questionnaires and analyzed univariately and bivariately with the Spearman Rank statistical test. Most of the students who have self-efficacy was in the middle level which was with a percentage of 58.9% and the students who have an interest in entrepreneurship was mostly in the high level with a percentage of 54.8%. From the results of statistical tests, there is a correlation (p <0.05) between self-efficacy with interest in student entrepreneurship with a moderate correlation (r = 0.534). Students' interest in entrepreneurship will increase if they have high self-efficacy. It is expected that students of the Applied Bachelor's Degree Program of Midwifery in Kediri can increase self-efficacy as an effective strategy for the stimulation of interest and entrepreneurship.